(untitled) (The Pakistan Development Review, 1996)
Using micro survey data obtained from a Punjab village we study a large number of rural-specific and household-specific variables besides landholding, in an attempt to determine their role in raising levels of living of rural masses. We investigated the reasons as to how some of the landless households managed to escape poverty whereas some cultivating households failed to do so. The main factors responsible for this outcome were found to be favourable/unfavourable distribution by size of landholding, household size, educational attainment, dependency ratio, participation rates, female-male ratio, and age of the household head. The landless households escaping poverty, however, remained in a low-income category. Whereas our analysis highlighted the importance of institutional setting for a better distribution of assets and access to resources, at the same time it pointed to the fact that numerous non-farm activities also enable the rural households to generate incomes and thus avoid poverty.